The effects of a downhill running bout on running economy - Braun, W. A.; Paulson, S. (Research in Sports Medicine, 2012)
This study investigated whether downhill (DH) running (10-min @ 214.4 m·min-1 and -10% grade) would elicit acute and delayed effects on running economy (RE) upon completion of DH running (RE2) and daily over 72 h (RE3, RE4, RE5). Fifteen runners (8 female, 7 male) completed the protocol. RE was measured during level running performed at 70% VO2peak. A baseline RE test (RE1) was used for comparison. Muscle soreness was significantly elevated at RE3 and RE4 vs. RE1. Oxygen uptake was significantly elevated at RE2 relative to RE3, RE4 and RE5 but was not different from RE1. Heart rate was similarly elevated at RE2. Measures of ankle, knee and hip joint angles at heel strike and toe off were not affected at any time-point in a subset of subjects (N = 6). A short DH running bout did not elicit significant delayed adverse effects on oxygen uptake or gait parameters relative to baseline.